The Emotional Experience of Members of Scotland's Citizens' Assembly on Climate Change - Andrews, Nadine (Frontiers in Climate, 2022)
In facing up to the reality of the climate crisis and the risks it poses, people encounter powerful emotions that can be difficult to bear. Consequently, various defences and coping strategies may be used to suppress or avoid feeling these emotions. The way in which emotions are regulated has important implications for wellbeing and decision-making. In recent years there has been growing interest in using citizens' assemblies to inform government climate policy. Assembly members learn about and discuss the subject, and produce recommendations for action. Given this element of learning about climate change, it is likely that difficult emotions will come up for assembly members. This paper investigates the emotional experience of members of Scotland's Climate Assembly to explore which, if any, emotions are experienced and how they are regulated. The findings are compared to a population survey, and discussed in relation to the assembly process including the evidence presented to members, and the assembly outputs. Assembly members appear to have had quite a different emotional experience compared to the general population, with higher levels of hopefulness and optimism, lower levels of worry and overwhelm, and a lower proportion reporting that their emotions about climate change were having a negative impact on their mental health. It is proposed that these differences in experience may in part be due to a focussed sense of purpose and agency that being an assembly member brings, along with exposure to evidence that may have underplayed the severity of the climate crisis and that was framed in ways that reassured the members that climate change can be tackled in an effective and fair way. However, after receiving the Scottish Government response to their recommendations, there are indications that levels of optimism and hopefulness dropped and levels of worry increased, with members expressing overall disappointment with the response. The findings enhance our understanding of how people perceive climate risk and how they experience that emotionally, and can be used to inform the design of future deliberative processes, and for supporting people to regulate their emotions about climate change and climate policy in an adaptive way.